Consequences of hydroxyl generation by the silica/water reaction Part I: Diffusion and Swelling - Fett, Theo (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2022)
Water diffusing into silica surfaces gives rise for several effectson diffusion behaviour and mechanical properties. Water added to silica glass increases its specific volume so that the silica expands near the surface. Mechanical boundary conditions give rise for compressive "swelling stresses". This fact provides a tool for the interpretation of many experimental observations from literature.